PERPUSTAKAAN ANAK SEBAGAI COMMUNAL SPACE DI KOTA BANJARBARU - Ike Rahayu Puji Astutik; J.C. Heldiansyah (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
As they grow, children have very broad imaginations. By frequently inviting children to read, watch educational videos or films that are appropriate for their age, they can increase their imagination. To respond to this, we need an informal educational forum that is both recreational and educational, namely a children's library as a communal space. This library is made as attractive as possible to encourage children to be happy and want to always come to the library and do reading activities while hanging out and how to make a children's library a place for education as well as recreation. From this it can be concluded that the method used uses a hybrid architectural approach as a design consideration in accommodating library functions which have two different functions. This is realized in the concept of collaborative space or spaces that are combined to create a flexible and mutually beneficial space and create an atmosphere for reading while gathering.